Effects of the COVID-19 Pandemic on Parental Burnout and Parenting Practices: Analyses Using a Retrospective Pretest. (July 2022) - Griffith, Annette K.; Bedard, Kasey E.; Eaton, Angeline; Ackerlund Brandt, Julie A.; Jha, Pragya
Background: Many of the conditions of the COVID-19 pandemic were consistent with factors shown to be predictive of parental stress and burnout. The purpose of the current study was to use a retrospective pretest method to gain an understanding of the effects of the COVID-19 pandemic on levels of parental burnout and on parenting practices. Method: A brief survey was conducted using a retrospective pretest method to examine parental burnout (The Parental Burnout Assessment, Roskam et al, 2018) and parenting practices (The Alabama Parenting Questionnaire, Frick, 1991). The survey asked parent participants to answer questions about their experiences before and during the pandemic. Results: Findings indicated that the pandemic had a significant impact on parents, increasing overall levels of parental burnout and impacting parenting practices by reducing use of positive parenting strategies and increasing use of inconsistent discipline and corporal punishment. These changes in parenting practices were even more pronounced for parents whose levels of parental burnout moved from "normal" levels before the pandemic to clinical levels during the pandemic. Conclusion: The findings of the current study suggest that the COVID-19 pandemic has had a negative impact on levels of parental burnout and parenting practices. Although additional research is needed, the results suggest that there is a need for clinicians to understand the effects that the pandemic may have had on parents and families with an understanding that families may be at ongoing risk despite a relaxation of COVID-19 restrictions.